2000
DOI: 10.3109/10611860008997899
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Introduction of Macromolecules and Oligonucleotides into Brain Capillary Endothelial Cells Using HVJ-Liposomes

Abstract: In this study, we examined the feasibility of introducing macromolecules into cultured mouse brain capillary endothelial cells (MBEC4 cells) by utilizing the hemagglutating virus of Japan (HVJ)-liposomes with fusogenic activity. We used fluorescein isothiocyanate dextran (FITC-Dextran) and FITC-labeled oligodeoxynucleotide (FITC-ODN) as models of a macromolecule and an ODN, respectively. Intracellular fluorescence appeared rapidly after the exposure of MBEC4 cells to FITC-Dextran-containing HVJ-liposomes, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
1
3
1
Order By: Relevance
“…6) in comparison with uncoated liposomes or plasmid alone. These results are consistent with our previous findings that HVJ-liposomes could introduce macromolecules into BCECs in vitro (Matsuo et al, 2000) and in vivo (unpublished data) more efficiently than uncoated liposomes. Therefore, the efficient expression of b-Gal gene is at least partly attributable to the effective introduction of the gene by HVJ-liposomes.…”
Section: Efficiency Of Transfer and Expressionsupporting
confidence: 95%
See 1 more Smart Citation
“…6) in comparison with uncoated liposomes or plasmid alone. These results are consistent with our previous findings that HVJ-liposomes could introduce macromolecules into BCECs in vitro (Matsuo et al, 2000) and in vivo (unpublished data) more efficiently than uncoated liposomes. Therefore, the efficient expression of b-Gal gene is at least partly attributable to the effective introduction of the gene by HVJ-liposomes.…”
Section: Efficiency Of Transfer and Expressionsupporting
confidence: 95%
“…Using the intra-arterial delivery of the HVJliposomes, we previously demonstrated efficient gene transfer into the carotid arterial wall in vivo and arterial endothelial cells in vitro (Yonemitsu et al, 1996). Moreover, we demonstrated that HVJ-liposomes can efficiently transfer macromolecules, such as fluorescein isothiocyanate dextran (FITC-dextran) and FITC-labeled oligodeoxynucleotide (FITC-ODN), into cultured brain capillary endo thelial cells (MBEC4 cells) in vitro (Matsuo et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that effective delivery of DNA mediated by the unmodified cationic polymers requires 3-6 h exposure [19]. However, our results showed an effective transfection in BCECs exposed to the Antp-modified nanoparticles occurred at 20 min, which was similar to the time-dependent manner of Tat-modified liposomes and HVJ-liposomes [4,20]. Such a rapid increase of intracellular DNA was not achieved by using simplex cationic DNA-polymer complexes, which were taken up via an endocytic mechanism [21].…”
Section: Discussioncontrasting
confidence: 54%
“…These results indicate that the gene was successfully transferred in vivo from HVJ-liposomes into BCECs, where it was expressed, and the gene product was secreted into the brain. Another study reported the in vitro uptake of HVJ-liposomes encapsulated fluorescein isothiocyanate-labeled dextran (FITC-dextran) and FITC-labeled oligodeoxynucleotide (FITC-ODN) by BCEC's (MBEC4 cells), indicating the utility of these fusogenic vesicles to transport macromolecules and oligonucleotides to BCEC's [60].…”
Section: Liposomesmentioning
confidence: 99%